Konsumsi Minuman Manis dan Perilaku Sedentari Mendorong Tren Kegemukan: Studi pada Remaja Perkotaan dan Pedesaan di Jawa Timur, Indonesia: Sweet Sweetened Beverages Intake and Sedentary Behavior Drive Overweight Trends: A Study of Urban and Rural Adolescents in East Java, Indonesia - Rifqi, Mahmud Aditya; Puspikawati, Septa Indra; Salisa, Wizara; Zaman, Md Nahid Uz (Amerta Nutrition, 2025)
Background: Overweight and obesity are growing concerns in developing countries, including Indonesia. Excessive food intake and lack of physical activity are major contributing factors to this issue. Objectives: This study aims to analyze the relationship between physical activity levels, dietary patterns, and nutritional status among adolescents living in rural and urban areas. Methods: This cross-sectional study involved 261 adolescents (120 males, 141 females) aged 12–14 years from East Java, Indonesia. Physical activity was assessed using the Physical Activity Questionnaire for Children (PAQ-C), while dietary intake was measured using daily recall and a food frequency questionnaire (FFQ). Nutritional status was determined based on BMI-for-age Z-scores. Results: More than 20% of adolescents were overweight (Z-score > 2), with a prevalence of 21% in rural areas and 31% in urban areas. Urban adolescents consumed more sugary drinks, had longer screen time, and slept less than their rural counterparts (p-value<0.05). Overall physical activity levels were significantly higher among rural adolescents. Key risk factors for overweight status included sugary drink consumption (OR 2.32), high-fat food intake (OR 1.61), low physical activity (OR 0.09), and prolonged screen time (OR 1.21). Conclusions: Differences in lifestyle between rural and urban adolescents impact their nutritional status. Targeted interventions to promote physical activity and reduce sugary drink consumption, especially in urban areas, are crucial for preventing overweight and improving adolescent health.